2020
DOI: 10.1200/jco.20.00793
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab or Placebo Plus Etoposide and Platinum as First-Line Therapy for Extensive-Stage Small-Cell Lung Cancer: Randomized, Double-Blind, Phase III KEYNOTE-604 Study

Abstract: PURPOSE Pembrolizumab monotherapy has shown antitumor activity in patients with small-cell lung cancer (SCLC). The randomized, double-blind, phase III KEYNOTE-604 study compared pembrolizumab plus etoposide and platinum (EP) with placebo plus EP for patients with previously untreated extensive-stage (ES) SCLC. METHODS Eligible patients were randomly assigned 1:1 to pembrolizumab 200 mg once every 3 weeks or saline placebo for up to 35 cycles plus 4 cycles of EP. Primary end points were progression-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
517
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 522 publications
(536 citation statements)
references
References 18 publications
17
517
2
Order By: Relevance
“…The literature search identified a total of 142 records, which, after vetting, resulted in a total of six phase III trials reporting efficacy outcomes on the use of ICIs for the treatment of ES‐SCLC (the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses diagram is shown in Fig. 1) [37, 39, 40, 43, 44, 48].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search identified a total of 142 records, which, after vetting, resulted in a total of six phase III trials reporting efficacy outcomes on the use of ICIs for the treatment of ES‐SCLC (the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses diagram is shown in Fig. 1) [37, 39, 40, 43, 44, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Four phase III trials assessed ICIs plus chemotherapy as first‐line therapy for ES‐SCLC (Table 1) [37, 40, 43, 48]. CA184 156 randomized patients to receive chemotherapy (etoposide 100 mg/m 2 and cisplatin 75 mg/m 2 or carboplatin area under the curve 5) every 3 weeks for four cycles plus either ipilimumab 10 mg/kg ( n = 478) or placebo ( n = 476) during cycles 3 and 4 followed by ipilimumab or placebo alone for cycles 5 and 6 then maintenance ipilimumab or placebo every 12 weeks for up to 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations